1997
DOI: 10.1002/(sici)1097-4628(19971128)66:9<1703::aid-app8>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Study of unsaturated polyester and vinylester morphologies using excimer laser surface treatment

Abstract: ABSTRACT:A technique based on the use of an ArF excimer laser (193 nm) to analyze the morphology of the unsaturated polyester and vinylester networks has been developed. This method is based on the use of the differences between the thresholds at which ablation of the various constituent phases of the materials occurs.After having determined the ablation threshold of a polystyrene, various surface treatments using excimer lasers fluence around this threshold were applied to unsaturated polyesters and vinylest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…It was also observed that with increasing cure temperature, the size of the microgels and clusters became smaller. The two-phase structure of VE matrices, unlike that of UPE resins, was found to be organized rather than random structured, which gives excellent hydrolytic stability to VE resins (Mortaigne et al 1997). Various methods employed to study the curing behavior of VERs are differential scanning calorimetry (DSC) (Chang 1992, Cook et al 1997, infrared (Ganem and Mortaigne 1993, Brill et al 1996, Li et al 1999, Brill and Palmese 2000, gel time studies (Abadie et al 2002), dynamic mechanical thermal analysis (DMTA) (Scott et al 2002a), torsional braid analysis (Stone et al 2000), and thermal scanning rheometry (Martin et al 2000).…”
Section: Curing Of Verssupporting
confidence: 55%
“…It was also observed that with increasing cure temperature, the size of the microgels and clusters became smaller. The two-phase structure of VE matrices, unlike that of UPE resins, was found to be organized rather than random structured, which gives excellent hydrolytic stability to VE resins (Mortaigne et al 1997). Various methods employed to study the curing behavior of VERs are differential scanning calorimetry (DSC) (Chang 1992, Cook et al 1997, infrared (Ganem and Mortaigne 1993, Brill et al 1996, Li et al 1999, Brill and Palmese 2000, gel time studies (Abadie et al 2002), dynamic mechanical thermal analysis (DMTA) (Scott et al 2002a), torsional braid analysis (Stone et al 2000), and thermal scanning rheometry (Martin et al 2000).…”
Section: Curing Of Verssupporting
confidence: 55%
“…As expected based on the work of Mortaigne [6] there should be a lower ablation threshold that should be surpassed during etching. Figure 1 shows a series of AFM height, amplitude and phase contrast images taken from the VE etched by different LA parameters.…”
Section: Results and Discussion 31 Laser Treatment (La)mentioning
confidence: 99%
“…Detectability of the morphology was prominently improved by physical etching. VE samples were etched by laser treatment [6] and argon ion (Ar + ) bombardment [7]. On the other hand, the nodules' size in the published works often differed from one another markedly.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This is one of the reasons why full conversion is impossible in isothermal conditions [11]. Although it is most often used, unpolar styrene is not a thermodynamically good solvent for relatively polar polyester [10,12,13], and so various saturated diacids or higher dialcohols are added in the preparation of polyesters to improve compatibility. Orthophthalic and isophthalic acids are the most often used diacids, because it is expected that their aromatic rings will increase compatibility with styrene, and the reactivity of the resin can be modified in that manner too, because polyester becomes less flexible and less reactive [14].…”
Section: Introductionmentioning
confidence: 99%